2012
DOI: 10.1175/mwr-d-11-00078.1
|View full text |Cite
|
Sign up to set email alerts
|

Possible Linkage between the Monsoon Trough Variability and the Tropical Cyclone Activity over the Western North Pacific

Abstract: The present study investigates the influence of the monsoon trough (MT) on the interannual variability of tropical cyclone (TC) activity over the western North Pacific during July–November for the period 1979–2007. It is shown that the TC activity is closely related to the MT location. During the years when the MT extends eastward (retreats westward), more (less) TCs form within the southeastern quadrant of the western North Pacific. Such a relationship can be explained by the changes in large-scale environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
167
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 186 publications
(185 citation statements)
references
References 55 publications
16
167
0
Order By: Relevance
“…The patterns in all simulated and BTD fields show characteristic anomalous TC activity in the south-eastern quadrant of the WNP during the positive phase and in the north-western quadrant during the negative phase. This spatial modulation of TC trajectories, as well as its impact on lifetime and TC maximum intensity, is the most distinguishable feature of the recorded interannual TC variability over the WNP (Camargo and Sobel 2005;Chan 2000;Wang and Chan 2002;Wu et al 2012). Nevertheless, not many modeling studies (Zhao et al 2007;Emanuel et al 2008) till now have shown a reasonable skill in reproducing interannual variability of TC frequency in this region.…”
Section: Simulated and Observedmentioning
confidence: 93%
See 1 more Smart Citation
“…The patterns in all simulated and BTD fields show characteristic anomalous TC activity in the south-eastern quadrant of the WNP during the positive phase and in the north-western quadrant during the negative phase. This spatial modulation of TC trajectories, as well as its impact on lifetime and TC maximum intensity, is the most distinguishable feature of the recorded interannual TC variability over the WNP (Camargo and Sobel 2005;Chan 2000;Wang and Chan 2002;Wu et al 2012). Nevertheless, not many modeling studies (Zhao et al 2007;Emanuel et al 2008) till now have shown a reasonable skill in reproducing interannual variability of TC frequency in this region.…”
Section: Simulated and Observedmentioning
confidence: 93%
“…But the authors were not able to reproduce the interannual variability of TC activity, mostly due to a weak/absent relationship with ENSO (Camargo et al 2007;Wang and Chan 2002). Wu et al (2012) examined the internal variability in downscaling simulations of the WNP climate, and reduced its impact by using an average over ensemble simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The variations of TC genesis frequency and intensity in the WNP, from intraseasonal to interdecadal time scales, are related to ISO phases (e.g., Gray 1979;Huang et al 2011;Li and Zhou 2013;, monsoon trough variability (e.g., Ritchie and Holland 1995;Chen et al 2004;Wu et al 2012), the El Niño-Southern Oscillation (e.g., Chan 2005;Du et al 2011;Kim et al 2011), and the PDO (e.g., Yang et al 2012;Liu and Chan 2013). WNP TC genesis frequency depends on the ISO phase ) and might also vary with different climate backgrounds of the EASM (Zhou et al 2009;Wang et al 2012) and PDO phase (Liu and Chan 2013).…”
Section: Did Anthropogenic Climate Change Influence the Extreme Tc Acmentioning
confidence: 99%
“…Moreover, the (1994), and c non-drought case year (2003). Shaded areas in a-c denote regions greater than 95% confidence level and negative regions, respectively TC genesis frequency in the SWNP is highly correlated with the western North Pacific summer monsoon (Chen et al 2004;Choi et al 2010;Wu et al 2012). Therefore, this study examines the relationship between the western North Pacific monsoon index (WNPMI, Wang and Fan 1999) and the drought severity in Korea, central China, and Japan (Fig.…”
Section: Influence Of Large-scale Atmospheric Circulation On Drought mentioning
confidence: 99%